Genotyping of Portuguese Chlamydia trachomatis urogenital isolates. Issue 6 (December 1997) - Borrego, M J; Gomes, J P; Lefebvre, J F; Eb, F; Orfila, J; Catry, M A
Abstract : OBJECTIVE: To determine the prevalence of the different Chlamydia trachomatis genotypes in Portuguese patients. METHODS: Urogenital isolates (n = 240) derived from attenders of various clinics in the Lisbon area were differentiated into genovars by genotyping with restriction fragment length polymorphism (RFLP) analysis of the PCR amplified omp1 gene. RESULTS: Genotype E was the most common for both men (47.9%) and women (43.8%). Genotypes D and F were the second most prevalent for men (11.3%) and genotype H was the second most prevalent for women (19.5%). Genotypes F, G, D, in women and H, G, I, in men, were found in a lower percentage of cases. Genotypes B, Ba, J, K, L1 and L2 were very rarely detected. CONCLUSIONS: With one exception, the overall distribution of Chlamydia trachomatis genotypes in our study is similar to what has been observed in other western countries. The only exception is the unusual prevalence of genotype H among women. The clinical manifestations associated with this and other genotypes were similar.